Pengembangan Media Zliqubo Untuk Meningkatkan Kecerdasan Visual Spasial Anak TK - Koesmadi, Dita Primashanti; Wijayanti, Arwendis; Rahayu, Elisa (Institut Agama Islam Negeri Ponorogo, 2021)
Development of Zliqubo Media (Quiet Book Puzzle) to Improve Visual Spatial Intelligence of Group B Kindergarten Children in Kwadungan District, Ngawi Regency. This study aims to: 1) Describe the effectiveness of Zliqubo (Puzzle Quiet Book) to improve the visual spatial intelligence of kindergarten children in group B in Kwadungan District, Ngawi Regency. 2) Describe the efficiency of Zliqubo (Quiet Book Puzzle) to improve the spatial visual intelligence of Group B Kindergarten children in Kwadungan District, Ngawi Regency. 3) Describe the attractiveness of Zliqubo (Puzzle Quiet Book) to improve the visual spatial intelligence of Group B Kindergarten children in Kwadungan District, Ngawi Regency. The research used was Borg & Gall Research and Development. The steps taken include analysis of potential and problems, data collection, product design, product validation, design revisions, product trials, product revisions. The product was tested on students through two stages of validation testing, namely a small group trial of 5 children and a large group trial of 15 children. The subject of the trial was the children of group B Kindergarten Dharma Wanita Dinden which consisted of a small group trial of 5 students and a large group trial of 13 students. Product viability is based on the results of the assessment of material experts, media experts and learning design experts. Data collection techniques using observation, interviews, and documentation. Data analysis in the form of quantitative descriptive. The results showed that the Zliqubo (Puzzle Quiet Book) which had been developed through a series of trials and expert validation was declared feasible. This is supported by expert material assessment with an average score of 3.42 included in the feasible category, assessment of experts with an average score of 3.7 including the feasible category, learning design expert assessment with an average score of 3.3 including eligible category. product trials get a percentage score (1) 100% of children can do activity I; (2) 93.75% of children can do activity II; (3) 87.5% of children can do activity III; (4) 89.7% of children easily carry out activities; (5) 94.86% of children are safe in playing activities with Zliqubo (Quiet Book Puzzle); (6) 92.30% of children feel happy when playing with Zliqubo (Puzzle Quiet Book). Based on the results of the research that has been done, it can be concluded that the Zliqubo (Puzzle Quiet Book) for the learning of Group B Kindergarten students in Kwadungan Subdistrict, Ngawi Regency is feasible to use.